Changes in the Religiosity of Secondary School Youth in Poland. A Sociological Analysis - Adamczyk, Tomasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The results of sociological studies on the transformation of religiosity indicate the deeper changes that have been taking place in this sphere in recent years. Therefore, it is worth paying attention to the religious transformations of the youth, as they can be regarded as a kind of barometer foreshadowing future development trends. The article shows the religiosity of secondary school students in Puławy. The empirical material used for the sociological analyses was collected during surveys carried out in 1994, 2009, 2016 and 2021, in the same secondary schools in Puławy, using the same survey questionnaire entitled “Secondary school graduates and moral values.” This article attempts to answer the research question of what changes have taken place over nearly 30 years in the religiosity of the surveyed youth, what direction these changes are taking and what is the pace of these changes. The following indicators were chosen to outline the religiosity of secondary school students: religious and religious self-declarations, religious practises, religious commitment.